Research on the influencing factors of users’ information processing in online health communities based on heuristic-systematic model - Gao, Yunyun; Gong, Liyue; Liu, Hao; Kong, Yi; Wu, Xusheng; Guo, Yi; Hu, DeHua (Frontiers in Psychology, 2022)
With the rapid development of the Internet and the normalization of COVID-19 epidemic prevention and control, OHCs have gradually become one of the important ways for people to obtain health information, and users have to go through a series of information processing when facing the massive amount of data. Understanding the factors influencing user information processing is necessary to promote users' health literacy, health knowledge popularization and health behavior shaping. Based on the Heuristic-Systematic Model (HSM) and Information Ecology Theory, we constructed a model of factors influencing user information processing in online health communities. We found that information quality and emotional support had indirect effects on heuristic information processing and systemic information processing, and these effects were mediated by privacy concerns and self-efficacy. Systematic information processing was most positively influenced directly by self-efficacy, and privacy concerns had a direct negative effect on both dual information processing pathways. Therefore, in order to promote user information processing, OHCs managers should develop relevant regulations to manage the quality of community information, improve community privacy protection services, provide an excellent interactive atmosphere for users, and strengthen their sense of self-efficacy.